2022
DOI: 10.1002/pri.1957
|View full text |Cite
|
Sign up to set email alerts
|

Thirty second chair stand test: Test–retest reliability, agreement and minimum detectable change in people with early‐stage knee osteoarthritis

Abstract: Background and Purpose: To determine intra-session test-retest reliability, agreement and minimum detectable change (MDC) of the 30 CST across three tests in people with knee osteoarthritis (OA). Methods:A test-retest reliability study was performed with 93 people with mild radiological knee OA. Participants were asked to complete three attempts of the 30 CST 1-2 min apart according to a standardised protocol. Participants completed three attempts on two occasions: baseline and 6 months later. Change between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
3
15
0
1
Order By: Relevance
“…Early evidence has supported the validity and reliability of a variety of physical assessments remotely performed in other populations [13,14,[30][31][32][33]. In our study, the remote 5STS test showed excellent reliability (ICC = 0.957) and no significant systematic errors were observed.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Early evidence has supported the validity and reliability of a variety of physical assessments remotely performed in other populations [13,14,[30][31][32][33]. In our study, the remote 5STS test showed excellent reliability (ICC = 0.957) and no significant systematic errors were observed.…”
Section: Discussionsupporting
confidence: 73%
“…The reliability (ICC) in other populations for the remote 5STS was also supportive, including among older veterans (remote assessments performed by two different assessors, ICC = 0.999) [14] and older adults (face-to-face vs. remote assessments, ICC = 0.960) [13]. The 30 s STS, is a variation of the 5STS test, and has also demonstrated similar reliability outcomes in knee osteoarthritis (ICC = 0.920) [30], cancer survivors and carers (ICC = 0.860) [32], and multiple sclerosis (ICC = 0.974) [31]. The SEM and MDC values of the 5STS test were 0.176 and 0.488 s, respectively.…”
Section: Discussionmentioning
confidence: 69%
“…The primary outcome was knee pain at 12 months according to the Knee injury and Osteoarthritis Outcome Score (KOOS) Pain scale. 9 Secondary outcomes were: 1) self-reported physical function (KOOS Function in Daily Living scale and KOOS Function in Sport and Recreation scale); 9 2) self-reported quality of life (KOOS Quality of Life scale 9 and EuroQol five-dimension five-level questionnaire); 10 3) self-reported knee joint stiffness (KOOS Symptoms scale); 9 4) self-reported global change in knee pain (7-point Likert scale); 7 5) six-minute walk test performance (6MWT); 11 6) 30-second chair stand test performance (30CST); 12 7) mental health (Hospital Anxiety Depression Scale (HADS)); 13 8) adverse events (Society of Interventional Radiology (SIR) Standards of Practice Committee adverse event classification); 14 and 9) change in pharmacotherapy to treat knee pain.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is important to note that these tests may not evaluate a single capability, and the interpretation may consider an overlap between muscle power and endurance, particularly between 30‐STS and 60‐STS. These tests have been reported that have good reliability 22–24 . The minimal detectable difference for TUG has been determined in 2.27 s 22 .…”
Section: Methodsmentioning
confidence: 99%
“…The minimal detectable difference for TUG has been determined in 2.27 s 22 . The minimal detectable difference of 30‐STS was established in one repetition, 23,24 and for 60‐STS in 3 repetitions 25 . The same physiotherapist (CD) performed the tests.…”
Section: Methodsmentioning
confidence: 99%